PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DENGAN MODERASI MOTIVASI KERJA (STUDI PADA DINAS ENERGI DAN SUMBER DAYA MINERAL KABUPATEN REMBANG DAN BADAN LINGKUNGAN HIDUP KA (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze the influence of OCB and organizational commitment on the job satisfaction, the influence of OCB, organizational commitment and job satisfaction on performance and the influence of OCB, organizational commitment and job satisfaction on performance moderated by motivation. Analysis tool used is multiple regression, as for testing the hypothesis using a t test. Data collection through questionnaires to measure using Likert scale of 7 (seven) alternative answers. Object of research is employees at Dinas Energi dan Sumber Daya Mineral in Rembang regency and employees at Badan Lingkungan Hidup in Rembang regency. Number of samples in this study were 83 respondents. Sampling technique using the purposive sampling. The results showed that (1) OCB have a positive and significant impact on job satisfaction, (2) organizational commitment have a positive and significant impact on job satisfaction, (3) OCB have a positive and significant impact on performance, (4) organizational commitment have a positive and significant impact on performance, (5 )job satisfaction have not effect on performance, (6)motivaton moderates the effect of OCB on performance, (7) motivation moderates the effect of organizational commitment on performance, (8) motivation moderates the effect of job satisfaction on performance, (9) job satisfaction does not mediate the effect of OCB on performance (10) job satisfaction does not mediate the effect of organizational commitment on performance. Key words: OCB, organizational commitment,motivation, job satisfaction and performance